(3eUfa GHf YHO GdQGRbs - (3YHO GdQGRb Hf geGe GdUZGfjs
(3ChdgG (B:s
(3jHJOF HHGH ZSd GdPQGYjf ef cJGH GdWgGQI s
(3BNQgG (B:s
(3jfJgi HHGH GdUjGe ai GdSaQ s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1712s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdMOjK h GdeUWdMs